2018
DOI: 10.1051/matecconf/201824503016
|View full text |Cite
|
Sign up to set email alerts
|

Temperature action in analysis of thermal stressed state of massive concrete and reinforced concrete structures

Abstract: The work is dedicated to research of the thermal stresses state of massive concrete and reinforced concrete structures in construction period. The article examines the results of the analysis of the thermal stress state, which occurs in massive concrete ground slab with thickness of 1 m. The study was conducted with using analytical models, which include the factor of diurnal temperature range in comparison with simplified methods. Authors established that solving the problem of thermal stressed state of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Developing and designing fire-resistant buildings is an effective way to prevent building fires. Makeeva et al [23] studied the thermal stress of mass-volume concrete and RC structures during construction, analyzed the thermal stress of 1m-thick mass-volume concrete floor slabs, and solve the thermal stress problem of large foundation slabs during construction under the condition of not taking the temperature change into consideration. Ashkezari and Razmara [24] studied the thermal expansion coefficient, mass loss, and residual compressive strength of conventional concrete and ultra-high performance fiber reinforced concrete (UH-PFRC) at high temperatures, and the results showed that the thermal expansion coefficient of UH-PFRC is larger than that of conventional concrete, the mass loss of UH-PFRC is also greater than that of conventional concrete after heating, the compressive strength of all samples decreases with the increase of heating temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Developing and designing fire-resistant buildings is an effective way to prevent building fires. Makeeva et al [23] studied the thermal stress of mass-volume concrete and RC structures during construction, analyzed the thermal stress of 1m-thick mass-volume concrete floor slabs, and solve the thermal stress problem of large foundation slabs during construction under the condition of not taking the temperature change into consideration. Ashkezari and Razmara [24] studied the thermal expansion coefficient, mass loss, and residual compressive strength of conventional concrete and ultra-high performance fiber reinforced concrete (UH-PFRC) at high temperatures, and the results showed that the thermal expansion coefficient of UH-PFRC is larger than that of conventional concrete, the mass loss of UH-PFRC is also greater than that of conventional concrete after heating, the compressive strength of all samples decreases with the increase of heating temperature.…”
Section: Introductionmentioning
confidence: 99%
“…For most of the large public buildings and special industrial structures, the key parts are generally built using new-type structures made of steel and concrete [1][2][3][4][5][6][7][8][9]. Although concrete structures have good corrosion resistance and durability, they are a kind of non-combustible material, and their mechanical properties are quite sensitive to temperature [10][11][12][13][14][15][16]. Since concrete structure buildings are prone to fire disaster with fast temperature rise and heavy smoke accumulation, once the temperature exceeds the limit temperature of steel and concrete, the structure of the building will be broken, and the bearing capacity and safety performance of the rest parts will be irreversibly weakened, thereby making the overall structure of the building be easily damaged or even collapse in severe cases [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%